2007
DOI: 10.1002/jmv.20812
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8 (HHV‐8) infection in healthy urban employees from Greece: Seroprevalence and associated factors

Abstract: A cross-sectional study was carried out in healthy company employees from Greece with the aim of assessing the prevalence of human herpesvirus 8 (HHV-8) and identifying risk factors for this herpesviral infection. Serum samples obtained from 955 subjects were tested for antibodies to HHV-8 by the K8.1 enzyme-linked immunosorbent assay (ELISA). Associations between HHV-8 serostatus and potential risk factors were examined using t-test, chi square test, and multivariate logistic regression analysis. HHV-8 preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
3
12
1
2
Order By: Relevance
“…Subjects aged 20–50 and > 50 had 63.3% and 144.5% higher risk for KSHV than those aged < 20 ( P = 0.009 and < 0.001, respectively). These results are consistent with those of several other studies, which described an increase of seroprevalence of KSHV with age in different populations [Baillargeon et al, 2001; Sitas et al, 1999; Sitas et al, 2001; Stein et al, 2004; Zavitsanou et al, 2007]. …”
Section: Discussionsupporting
confidence: 93%
“…Subjects aged 20–50 and > 50 had 63.3% and 144.5% higher risk for KSHV than those aged < 20 ( P = 0.009 and < 0.001, respectively). These results are consistent with those of several other studies, which described an increase of seroprevalence of KSHV with age in different populations [Baillargeon et al, 2001; Sitas et al, 1999; Sitas et al, 2001; Stein et al, 2004; Zavitsanou et al, 2007]. …”
Section: Discussionsupporting
confidence: 93%
“…All the above mentioned data triggered the study of the seroprevalence of HHV-8 in healthy blood donors in Greece. It has been previously reported that the prevalence of HHV-8 in the general population in Greece is 7.6% and that the seropositivity for HHV-8 was associated with a history of endoscopic procedures and HBsAg positivity [8]. Nevertheless, we found no blood donor tested positive for HHV-8 IgG antibodies.…”
Section: Discussioncontrasting
confidence: 56%
“…Further analysis of the risk factors associated with KSHV indicated that KSHV infection was associated with advancing age, low education level, and stationary population status. These results are consistent with those of several other studies, which described an increase in seroprevalence of KSHV with age in different populations (Baillargeon et al, 2001;Zavitsanou et al, 2007;. This correlation may be related to the natural aging process, and hypoimmunity may be a promoting agent for KSHV infection.…”
Section: Discussionsupporting
confidence: 93%